Evaluation of the Bangga Mbangun Desa Policy in Improving Regional Development in Cilacap Regency, Central Java - Aprianto, Naerul Edwin Kiky; Meliana, Rini (Badan Riset dan Inovasi Daerah Provinsi Kalimantan Selatan, 2024)
The gap between regions is the main issue that underlies the current national regional development, especially between urban and rural areas. To minimize this problem, policies that focus on accelerating development evenly are needed. In this case, the local government of Cilacap Regency is guided by the Bangga Mbangun Desa policy as an effort to accelerate the development of the Cilacap area, especially in rural areas by using a descriptive-qualitative research method sourced from the performance report of Cilacap Regency government agencies and public policy evaluation theory, this study aims to analyze Bangga Mbangun Desa as a policy in improving regional development. The results of this study show that in order to improve the development of the Cilacap Regency region, the Bangga Mbangun Desa policy, which is regulated in Regent Regulation No. 76/2011. Bangga Mbangun Desa focuses on four pillars, namely education, health, economy, and socio-cultural environment. Seeing regional development through Proud to Build Villages, this policy emphasizes the process of structured agrarian development (agriculture), especially in rural areas. Local governments give authority to village governments to manage and regulate their respective villages. This is manifested in innovative programs such as poverty alleviation through integrated data-based development planning; Barriers to response time; farmer stalls; Simbaja; Then Eat TB RO; Cerdas Kir Bang Bade; and a breakthrough tourism health center with child- and disability-friendly services.